Enhancing Understanding of Ethical Product Photography: Mitigating Ambiguity in Online Commerce - Mohamad Torik Langlang Buana; Fardinal Fardinal; Deden Tarmidi (Universitas Muhammadiyah Sidoarjo, 2023)
In the realm of online commerce, product photography serves as a vital means of introduction and presentation for sellers, significantly impacting the purchasing decisions of potential buyers. High-quality and ethically crafted product photos are not only beneficial to sellers but also uphold principles of transparency and fairness in accordance with Islamic economic ethics. This community engagement initiative aimed to enhance foundational knowledge regarding ethical product photography, ultimately ensuring that product images accurately represent the goods being sold, thus avoiding potential misunderstandings that may arise from misleading visuals in advertisements. The methodology involved educating participants about the concept of